Enhancing Methane Production in a Two-Stage Anaerobic Digestion of Spent Mushroom Substrate and Chicken Manure via Activation of Sludge, Optimization of Temperature, and C/N Ratio - Shu, Chin-Hang; Jaiswal, Rajan; Kuo, Mu-do; Yu, Bing-Hung (Frontiers in Environmental Science, 2022)
Management of spent mushroom substrate (SMS) is causing a global environmental concern due to tremendous increase in mushroom production globally. Therefore, in this research, the performance of a two-stage anaerobic co-digestion (TS-AD) of spent mushroom substrate and chicken manure was evaluated in terms of methane and biogas production and process stability with respect to single stage anaerobic digestion (SS-AD). Activation of anaerobic sludge using aeration or heat treatment in the first stage at mesophilic temperature followed by thermophilic co-digestion with chicken manure in the second stage was investigated. TS-AD exhibited better performance and enhanced methane generation over SS-AD. The optimal temperatures were determined as 35°C and 50°C for the first and the second stage of TS-AD, respectively. C/N ratio of 10 was the most suitable for biogas and methane production. TS-AD with C/N ratio of 10 and mesophilic digestion of SMS and sludge for 3 days at 35°C followed by co-digestion of the first stage effluent with chicken manure at 50°C was the optimized state producing 1359 mL of biogas of which 614.42 mL was methane, showing an increment by 59.44% in methane production as compared to SS-AD. TS-AD might be promising approach for utilization of SMS as feed stocks for biogas and methane production.